La competitividad en el servicio al cliente en la empresa de banquetes "La Avellana" ubicada en Morelia, Michoacán - Carrillo López, Laura (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
Based on the Theory of the Competitiveness that was developed by Michael E. Porter in 1990, it is known that there are many factors in order to maintain and improve the participation of companies in the market. For the purposes of this research, we analyzed factors that had a greater impact on competition in the customer service in the company of Banquet facilities "La Avellana", located in Morelia, Michoacán considering the factors of higher frequency. Determining thereby that the variables of Strategic Alliances, Marketing, Human Capital and infrastructure were the indicated variables to achieve the competitiveness of the company “La Avellana” Banquet facilities in the city of Morelia, Michoacán. To obtain the information were collected using a questionnaire with 16 questions to a sample of 138 people, considering a accuracy of 95 %, in the research that they conducted to the customers and gave us a reliability coefficient of 0,977 It was also applied an instrument with 16 questions to the experts who are entrepreneurs and business owners at receptions in the city of Morelia is say the direct competition of the enterprise "La Avellana" banquet facilities in order to determine whether the variables analyzed consider important for the competitiveness of your business was obtained a reliability coefficient of 0,965 in a sample of 37 business where replied 30 makers. The results show that the variables analyzed in this research, have a direct positive correlation and therefore have a greater impact on our variable of competitiveness in the customer service in the business of banquet “La Avellana".

Partiendo de la Teoría de la Competitividad que fue desarrollada por Michael E. Porter en 1990, se tiene conocimiento de que existen muchos factores para lograr mantener y mejorar la participación de las empresas en el mercado. Para efectos de esta investigación, se analizaron factores que tenían un mayor impacto en la competencia en el servicio al cliente en la empresa de Banquetes “La Avellana”, ubicado en Morelia, Michoacán considerando los factores de mayor frecuencia. Determinándose así que las variables de Alianzas Estratégicas, Marketing, Capital Humano y la Infraestructura eran las variables indicadas para lograr la Competitividad de la empresa “La Avellana” Banquetes ubicada en la ciudad de Morelia, Michoacán. Para obtener la información se aplicó un cuestionario con 16 preguntas, a una muestra de 138 personas, considerando una precisión del 95%, en la investigación que se les realizo a los clientes y nos dio un coeficiente de confiabilidad de 0.977. También se aplicó un instrumento con 16 preguntas a los expertos que son los empresarios y dueños de empresas Banqueteras en la ciudad de Morelia es decir la competencia directa de la empresa “La Avellana” Banquetes de manera que se pudiera determinar si las variables analizadas las consideran importantes para la competitividad de su Negocio se obtuvo un coeficiente de confiabilidad de 0.965 en una Muestra de 37 negocios donde contestaron 30 encargados. Los resultados muestran que las variables analizadas en esta investigación, presentan una correlación directa positiva y por ende tienen un mayor impacto sobre nuestra variable de competitividad en el servicio al cliente en el negocio de Banquetes “La Avellana”.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2013-1338; Negocio; Banquete; Alianzas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6012